Travel Notes from the New Literacy Studies Instances of Practice - Pahl, Kate; Rowsell, Jennifer (Multilingual Matters, 2006)
This book joins two important fields, that of literacy and multimodality, with a focus on local and global literacies. Chapters include work on media, popular culture and literacy, weblogs, global and local crossings, in and out of educational settings in such locations as the US, the UK, South Africa, Australia and Canada
Description based on online resource; title from PDF title page (publisher's Web site, viewed 25. Jul 2018)
Keywords: literacy practices; literacy studies; multimodal literacies; multimodality; New Literacy Studies; South Africa; South Australia; Globalization; Literacy; Technological literacy; Schreib- und Lesefähigkeit; Globalisierung; Aufsatzsammlung